Facile synthesis of hierarchical Co3O4/MWCNT composites with enhanced acetone sensing property. Issue 19 (1st October 2022) - Fu, Qiang; Lyu, Pengfei; Handschuh-Wang, Stephan; Teng, Long; Zheng, Bo
Abstract: A facile hydrothermal approach is reported for the preparation of a series of hierarchical cobalt tetraoxide (Co3 O4 )/multi-walled carbon nanotube (MWCNT) composites with different MWCNT amount. The material characterization reveals that the broccoli-like nano-agglomerates of Co3 O4 nanoparticles are anchored to the surface of the intertwined MWCNT network structure in all the Co3 O4 /MWCNT composites. The optimized Co3 O4 /MWCNT based chemiresistive sensor has ultralow limit of detection of 0.41 ppm, and up to 5 times greater sensing response than the pristine Co3 O4 based sensor while exposed to 100 ppm of acetone gas at 140 °C. The Co3 O4 /MWCNT based sensor has a short response time of 15 s and a short recovery time of 18 s, respectively. In addition, the Co3 O4 /MWCNT based sensor presents long-term stability, good reproducibility and high selectivity. The possible mechanisms of the enhanced chemiresistive response of the composite include the formation of the p-p hetero-junctions at the interface between Co3 O4 and MWCNT, the increased amount of adsorbed oxygen species on the composite surface, and the mesoporous structure of the composite.